Pengaruh Kegiatan Kolase Berbahan Bekas Terhadap Kemampuan Motorik Halus Anak - Ndolan, Yusmerni; Nur Zuama, Shofiyanti; Akbar, Mohamad; Agusniatih, Andi (UNIB Press, 2025)
This study aims to examine the effect of collage activities using recycled materials on fine motor skills development in children from group B1 at TK Bungamputi Palu. The research subjects consisted of 15 early childhood students. A descriptive quantitative method was employed with data collection techniques including observation, interviews, and documentation. Data were analyzed using percentage formulas and paired sample t-tests. The results demonstrate significant improvement in fine motor skills following the implementation of collage activities using recycled materials. The calculated t-value of -8.404 appeared negative because the pre-treatment mean was lower than the post-treatment mean. When interpreted positively, the t-calculated value of 8.404 exceeded the t-table value of 1.761, leading to the rejection of H0 and acceptance of H1. This indicates a significant effect of collage activities using recycled materials on children's fine motor skills development in group B1 at TK Bungamputi Palu. Based on the comparison table, the significance value of 0.000 < 0.05 meets the decision criteria for paired sample t-tests, confirming that collage activities using recycled materials have a significant positive effect on fine motor skills development in children from group B1 at TK Bungamputi Palu.